Mengukur Citra Carrefour Bg Junction Di Kota Surabaya - Erida Nursiana; Aridha Prassetya; Achmad Daengs GS; Mahjudin Mahjudin; Diana Zuhro (Jurnal Mahasiswa Manajemen dan Akuntansi, 2023)
This research aims to determine the image of Carrefour Bg Junction Surabaya from the perspective of consumers. The sample used was 35 people consisting of 35 hope questionnaires and 35 performance questionnaires. Determining the sample in this study used probability sampling with proportional sample strata. The results of the analysis using the Importance Performance Analysis (IPA) method show that the image of Carrefour Bg Junction Surabaya is quite good in the eyes of consumers. This can be seen in the results of the IPA map graph which consists of 6 variables, namely the service provided by employees, the quality of the products sold, the product choice variable, the retail atmosphere variable, the comfort variable and the value/price factor. Where the service variables provided by employees and the retail atmosphere variables are considered important and are expected to be supporting factors for consumer satisfaction, so that Carrefour Bg Junction Surabaya is obliged to ensure that the performance of the stores managed can continue to maintain the achievements that have been achieved. Apart from that, there are 4 other variables, namely the quality of the product sold, product choice, convenience and value/price factors which are considered to influence consumer perceptions which are less important but the implementation is excessive and considered less important but very satisfying.